The CND-Goiaba 1.0 software for nutritional diagnosis of guava (Psidium guajava L.) 'Paluma', in Brazil - Rozane, D. E. [UNESP]; Natale, W. [UNESP]; Parent, L. E.; Dos Santos, E. M H [UNESP] (My University, 2012)
Computer programs enable the transformation of raw data into useful information for decision making in many fields, including agriculture. Various programs have been developed to assist farmers to make better decisions about crop management practices and plant nutrition parameters. This article introduces the CND-Goiaba 1.0 software (C Sharp) and its use as a tool to perform the mathematical calculations involved in determining the compositional nutrient diagnosis (CND) indexes for the guava tree. This program was developed in Brazil, the world's leading producer of red guavas. A database was created based on 205 leaf samples collected in commercial plots (sampling units) of cultivated 'Paluma' guava trees (Psidium guajava L.) with ages between 5 and 20 years, during the 2009-2010 and 2010-2011 growing seasons. The production data were normally distributed according to the Shapiro-Wilk test (W=0.988; p=0.11). The software made it possible to diagnose that 63% of the orchards evaluated needed to improve the nutritional status of their trees. The CND method showed severe nutritional imbalances in Mg and Zn in these orchards. © ISHS.
Keywords: CND; Computer program; Leaf analysis; Mineral nutrition; Psidium; Psidium guajava